Associations of Chronotype, Work Schedule, and Sleep Problems With Work Engagement Experiences in Middle Age-The Northern Finland Birth Cohort 1966 - Kiema-Junes, Heli; Saarinen, Aino; Ala-Mursula, Leena; Hintsanen, Mirka (Lippincott Williams and Wilkins Ltd., 2024)
OBJECTIVE: The aim of the study is to investigate the role of chronotype for work engagement in middle age. METHODS: We used data from the Northern Finland Birth Cohort 1966 study ( N = 5341) to analyze associations of self-reported chronotype (morning, intermediate, and evening type) with work engagement and its dimensions (vigor, dedication, absorption). We conducted multivariate analyses of variance to examine whether work schedule or sleep problems moderate these associations. RESULTS: Evening types showed lower scores in work engagement and its dimensions than intermediate and morning types, even when work schedule and sleep problems were controlled. Sleep problems emphasized the chronotype-work engagement and chronotype-dedication linkages. CONCLUSIONS: Chronotype may play a role in employees' work engagement. In addition, sleep problems seem relevant in terms of chronotype-work engagement linkage. Peer reviewed